Two new surprising species of leaf-litter toad of the Rhinella margaritifera species group (Anura: Bufonidae) from the Peruvian Amazon, Loreto—Peru - Rojas, Rommel R.; Peña, Pedro Perez; Ávila, Robson W.; de Carvalho, Vinicius Tadeu; Perez, Renata; Farias, Izeni Pires; Gordo, Marcelo; Hrbek, Tomas (Zootaxa, 2022)
We describe two new species of Rhinella (Anura: Bufonidae) from the department of Loreto, Peru. We integrate morphological and phylogenetic analyses to provide evidence of new species. R. angeli sp. nov. is diagnosable from all congeners by its pronounced fleshy proboscis and R. unapensis sp. nov. by the small size (mean snout-vent length=37.7 ± 4.1 mm) of adult males, snout pointed in dorsal view, nearly acute in lateral view, and small bony protrusion at the angle of jaws among other characters. The two species are allopatric, where the first species is known to be associated inhabits upland (=terra firme) forests, while the second white sand forests (=varillales) around Iquitos city. The two new species represent the 20th and 21st species of the Rhinella margaritifera species group.